2013
DOI: 10.15296/ijwhr.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Activity Evaluation of Ginger Rhizome inReducing Depression in the Forced Swimming Test of RatsExposed to Electromagnetic Field (EMF)

Abstract: Objective: Ginger has always been known as one of the most famous medicinal herbs in eastern Asia (China and India). In this study we examined the effects of antidepressants-like activity of Ginger on the protection of central nervous system against oxidative damages. Material and Methods: Male Wistar rats (n=30) were allocated into three groups, control (n=10) and test groups (n=20) that subdivided into groups of 2 that had been exposed to 50 Hz electromagnetic fields (EMFs) for 8 weeks, one of the test group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Moreover, supplementation with ginger has been shown to reduce symptoms of anxiety and depression in human 48,49 and animal studies. 50,51 Therefore, the amelioration of psychological QoL in this study may be caused by the anti-anxiety and anti-depressant effects of ginger. These effects seem to be mediated through serotonergic pathways.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, supplementation with ginger has been shown to reduce symptoms of anxiety and depression in human 48,49 and animal studies. 50,51 Therefore, the amelioration of psychological QoL in this study may be caused by the anti-anxiety and anti-depressant effects of ginger. These effects seem to be mediated through serotonergic pathways.…”
Section: Discussionmentioning
confidence: 81%
“…[24,25] However, true mechanism of antidepressant effect of the Ginger is still unknown but behavioral parameters in forced swimming test confirmed potential antidepressant effect as serotonergic agents. [26,27] The antidepressant effect of thymoquinone (active constituent of Nigella sativa) by increasing 5-HT concentrations which in turns modulate/down regulate the swim or hanging stress induced serotonergic dysfunction. The synaptic enhancement of monoamine level, predominantly 5-HT, is the key pharmacological mechanism of the anti-depressant effect.…”
Section: Discussionmentioning
confidence: 99%
“…As stated in the Introduction, ginger extracts and 6-gingerol exert antidepressant-like effects in rat and mouse models. 5,2 The majority of active constituents of ginger are phenolic in nature. Several earlier studies showed that TDO activity is inhibited in vitro by phenols, such as catechol, dihydroxyphenylalanine, epinephrine, 5-HTP, norepinephrine, resorcinol and salicylate.…”
Section: Discussionmentioning
confidence: 99%
“…4 and its pattern of behavior in the forced swimming test resemble that of serotonergic antidepressants. 5 The bioflavonoid quercetin is abundant in Ginger. 6 and is known to exert a wide range of behavioral effects, such as anxiolytic and antidepressant.…”
Section: Introductionmentioning
confidence: 99%